BdVRN1 Expression Confers Flowering Competency and Is Negatively Correlated with Freezing Tolerance in Brachypodium distachyon - Feng, Ying; Yin, Yanhai; Fei, Shuizhang (Frontiers in Plant Science, 2017)
Vernalization is an essential process by which many temperate plant species acquire competence for flowering. Brachypodium distachyon is a model plant for temperate grasses including many cool-season forage and turfgrasses and cereals. Grasses with spring growth habit do not require vernalization for flowering and are typically less winter hardy. Yet the connection between vernalization and freezing tolerance remain unclear. The diverse requirement of vernation for flowering make it an ideal choice for studying the relationship between vernalization and freezing tolerance. Here, we isolated and analyzed the spatial and temporal expression patterns of two vernalization related homologous genes, BdVRN1 and BdVRN3 in Bd21, a non-vernalization- requiring accession, and Bd29-1, an accession shown to be vernalization-requiring. We showed that expression of BdVRN1 and BdVRN3 is independent of vernalization in Bd21, but is vernalization dependent in Bd29-1. Moreover, vernalization- induced expression of BdVRN1 appears to precede that of BdVRN3 in Bd29-1. Bd21 RNAi knockdown mutants for BdVRN1 conferred vernalization requirement for flowering, and reduced the expression of BdVRN3. Both Bd29-1 and the BdVRN1 RNAi mutants of Bd21 exhibited reduced freezing tolerance upon vernalization treatment. Cold responsive genes BdCBF2, BdCBF3, BdCBF5, BdCBF6, and BdDREB2A were all constitutively expressed at a high level in the BdVRN1 RNAi mutants of Bd21. Taken together, our results suggest that expression of BdVRN1 promotes flowering by upregulating BdVRN3, and gaining the competency for flowering reduces freezing tolerance in Brachypodium.